Translation Studies in the 21st Century: Trends, Challenges, and Future Directions - Yadav, Harshita (Journal of Advanced Research in English & Education; Vol 9 No 4 (2024): Journal of Advanced Research in English and Education, 2024)
Translation Studies has evolved significantly in the 21st century, driven by technological advancements, globalization, and increasing cultural exchange. This article reviews key trends, challenges, and future directions in the field. It highlights the impact of machine translation, the rise of interdisciplinary approaches, the emphasis on cultural sensitivity, and the ongoing challenges of ethical translation practices. The transformative role of artificial intelligence, particularly neural machine translation, is discussed alongside its implications for professional translators and language accessibility. Additionally, the article explores how the discipline has responded to the demands of localization and the preservation of linguistic diversity in a rapidly globalizing world. The article concludes by proposing areas for future research and development, emphasizing the role of education, technology, and collaboration in shaping the future of Translation Studies, with a call to address ethical dilemmas, support low-resource languages, and enhance translator training programs to meet the demands of a dynamic, interconnected society.